Investigating the performance of PVA and basalt fibre reinforced beams subjected to flexural action - Shafiq, N. (Elsevier Ltd, 2016)
This paper presents the flexural test results of 21 fibre reinforced concrete (FRC) beams containing PVA and basalt fibres (1-3 by volume). Fibre reinforced concrete was made of three different binders; the first binder type was 100 cement, the other two types were blended cement system containing a part of 10 silica fume or metakaolin with 90 cement. For each the three binder system; 7 beams of the size 100 Ã 200 Ã 1500 mm were cast, the first beam known as control beam contained no fibres. The remaining 6 beams were cast using FRC containing a volume fraction of 1, 2 and 3 PVA and basalt fibres, respectively. All 21 beams were tested to failure under three-point flexural loading. Experimental results showed that the addition of PVA fibres significantly improved the post-cracking flexural response compared to that of the basalt fibres. Beams with 3 PVA fibre volume showed deflection-hardening behaviour with an improvement in post-cracking flexural strength. It means that the addition of high volume content of PVA fibres made the beams more tough and ductile. Whereas, deflection-softening behaviour was observed in case of beams containing higher volume of basalt fibres. Â© 2016.